Acrolein-inducing ferroptosis contributes to impaired peripheral neurogenesis in zebrafish - Qi, Haozhe; Kan, Kejia; Sticht, Carsten; Bennewitz, Katrin; Li, Shu; Qian, Xin; Poschet, Gernot; Kroll, Jens (Frontiers in Neuroscience, 2023)
Introduction Diabetes mellitus (DM) is associated with physiological disorders such as delayed wound healing, diabetic retinopathy, diabetic nephropathy, and diabetic peripheral neuropathy (DPN). Over 50% of diabetic patients will develop DPN, characterized by motor dysfunction and impaired sensory nerve function. In a previous study, we have uncovered acrolein (ACR) as an upstream initiator which induced impaired glucose homeostasis and microvascular alterations in zebrafish. Whether ACR has specific effects on peripheral neurogenesis and mediates DPN, is still waiting for clarification. Methods To evaluate the function of ACR in peripheral nerve development, in vivo experiments were performed in Tg(hb9:GFP) zebrafish. In addition, a series of rescue experiments, metabolomics assessment, and bioinformatics analysis was performed aimed at identifying the molecular mechanisms behind ACR’s function and impaired neurogenesis. Results Impaired motor neuron development was confirmed in wild-type embryos treated with external ACR. ACR treated embryos displayed ferroptosis and reduction of several amino acids and increased glutathione (GSH). Furthermore, ferroptosis inducer caused similarly suppressed neurogenesis in zebrafish embryos, while anti-ACR treatment or ferroptosis inhibitor could successfully reverse the detrimental phenotypes of ACR on neurogenesis in zebrafish. Discussion Our data indicate that ACR could directly activate ferroptosis and impairs peripheral neurogenesis. The data strongly suggest ACR and activated ferroptosis as inducers and promising therapeutic targets for future DPN studies.